Magnetite–Hematite Characterization at Micron Scale with Implications for Metallurgical Processing and Decarbonization - Beate Orberger; Christiane Wagner; Omar Boudouma; Nicolas Rividi; Christine Bauer; Rebecca Wagner; Ghasem Nabatian; Maryam Honarmand; Iman Monsef (Materials Proceedings, 2023)
Magnetite deposits represent important iron ore resources. Selective sorting of valuables from gangue and targeting of potential critical metals that can be recovered from waste streams must be implemented from the exploration and excavation steps onwards. Optical and scanning electron microscopy, electron microprobe analysis, dual-energy X-ray transmission, and computed tomography were applied to determine the mineralogy and classify the iron oxides of different iron ore types. These characteristics can be used for sorting at the exploration and extraction steps to reduce unvaluable materials at the loading and hauling steps, which contribute about 50% of the greenhouse gas emissions of the iron ore mining and mineral processing sector. These data also contribute to fine-tuning mineral processing parameters.